Application of the Resource Base View-Based Artificial Intelligence Model to Create Competitive Advantage for MSME Exports in Pontianak City - Hasibuan, Rizki Alfitra; Hasbyanti, Hasbyanti; Fariyanda, Rosan; Jeffy, Izha Fadlam; Narandi, Thomas (PT FORMOSA CENDEKIA GLOBAL, 2024)
The performance of Indonesian MSMEs plays an important role in economic growth, with their contribution to GDP reaching 60.34% in 2017. However, Indonesian MSMEs still face challenges, such as low product quality and limited competitiveness, especially in the global market. One proposed solution is the Resource-Based View (RBV) method to improve the competitive advantage of MSMEs. This research develops an RBV model with the support of Artificial Intelligence (AI) technology, aimed at mapping the strategic resources of MSMEs. This research focuses on Pontianak City MSMEs that have carried out export activities analyzed using the Analytical Hierarchy Process (AHP) method. This research created an RBV-based AI framework to assess and manage strategic resources to gain competitive advantage.